Exegesis of the Book of Isaiah 61:1–11: Redaction Criticism and Inquiry into the Identity of the Prophet Known as Trito-Isaiah - Slawik, Jakub (Collectanea Theologica, 2021)
The exegesis of Isa 61 demonstrated that the chapter is a separate composition, which comprises a framing device in vv. 1–3.10.11, and a middle section in vv. 4–9. This section did not have to originate as a single fragment. From the literary-critical standpoint, the suspect element is v. 3aa, which currently serves to connect Isa 61 with the adjacent chapters 60, and 62. However, it is best to interpret the pericope as a single whole, with the speaker being the prophetic “I,” stylised after the servant-prophet from the Deutero-Isaiah’s Songs of the Servant of the Lord. Behind this “I,” there are probably the tradents of Deutero-Isaiah’s traditions, updating his promises and adding new ones. In that case, the prophet Trito-Isaiah, who was to be reminiscent of the earlier prophets, speaking before the people, never existed. That, however, does not alter the fact that the tradents did consider themselves to be the servant of the Lord, and regarded their mission to be a prophetic one.